ANALISIS EFEKTIVITAS PENYEWAAN MOBIL TERHADAP PERUSAHAAN STARTUP - Indrajaya, Fransiskus Dion (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
The development of companies in Indonesia is happening a lot after the Covid-19 pandemic began to subside. Many business people who have started to open their companies which are commonly referred to as startup companies have started to appear in Indonesia. Startup companies are start-up companies that have recently been operating and are in the development stage. This company usually starts with ordinary capital, therefore, the owner of the company will suppress capital. One way is to use a car rental service for the company's mobility needs. This is done to avoid car maintenance costs and car taxes. In order for car rental services to be in demand, car rental service companies must balance the quality of the vehicles being rented as well as the driver services provided as well as affordable prices. In terms of vehicles, the vehicles for rent are in good condition and clean. Meanwhile, in terms of the services of the drivers being rented, the drivers must have good driving skills and have a good nature and be friendly to users of car rental services. Therefore, the effectiveness of using this car rental service must also be maintained properly so that it can be more attractive to business people who are starting to build their startup company. Keywords: startup, vehicle, driver, effectiveness